Low-casting, low-smoke, halogen-free and flame-retardant TPU cable material and preparation method thereof
By using specific raw materials and additives in the TPU cable material, prepare TPU cable materials with low -current, low -tobacco -halogen -free flame retardant characteristics, solve the problem of delay in the process of modification TPU, realize the cable material, and achieve the cable material. Stable processing and high safety.
Patent Information
- Application Number
- CN202411725308.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-28
AI Technical Summary
The modified TPU has casting phenomenon during processing, resulting in unstable shape of the cable material, uneven surface, and even cracks or fractures.
By selecting appropriate raw materials and additives, prepare TPU cable materials with low delay characteristics. Specific methods include the use of phenyl -phenol dihydroxyl -based ether, polyphyl hydrogen bephyethyl ether, and organic polyether polyol to synthesize TPU precursor A, which are mixed with nano hydroxide. At the same time, the compatibility agent, dispersant, and inorganic filling charged, through specific preparation steps and process conditions, form a TPU cable material with low flow delay, low -smoke and halogen -free flame retardant.
The excellent liquidity of the TPU cable material in the melting state, meet the processing requirements of the cable manufacturing process, improve the production efficiency and reduce production costs. At the same time, the cable materials have excellent performance such as low -flow delay, low smoke and halogen -free flame retardant, which improves the safety and reliability of the cable.
Smart Images

Figure BDA0005159063110000051 
Figure BDA0005159063110000061 
Figure BDA0005159063110000062
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cable materials, and in particular to a low-casting, low-smoke, halogen-free, flame-retardant TPU cable material and a preparation method thereof. Background Art
[0002] Cable materials are key materials in the production of wires and cables. Their quality and performance directly affect the insulation, sheath and other characteristics of wires and cables. With the enhancement of environmental awareness and the government's emphasis on safe production, environmentally friendly cable materials such as low-smoke halogen-free wire and cable materials are gradually favored by the market. This type of cable material is environmentally friendly and highly safe, and has been widely used in electricity, communications, construction and other fields.
[0003] In the related art, TPU is modified to become a cable material with low-smoke, halogen-free, flame-retardant and other properties. During the cable manufacturing process, when a cross-linking agent is used to cross-link with other low-smoke halogen-free materials such as modified TPU, due to its special chemical composition and cross-linking mechanism, this type of material is often difficult to control during the processing and is prone to casting. The "casting" phenomenon here refers to excessive fluidity and ductility during the processing, especially during extrusion molding, which may cause the cable material after extrusion to have an unstable shape, an uneven surface, and even cracks or breakage.
[0004] In order to control and reduce the casting phenomenon of modified TPU during the processing, to ensure that the cable material can be stably and efficiently extruded and molded, thereby manufacturing high-quality and high-safety wire and cable products, a low-casting, low-smoke, halogen-free flame-retardant TPU cable material and a preparation method thereof are provided. Summary of the invention
[0005] In order to solve the casting problem existing in the processing of modified TPU in the related art, the present application provides a low-casting, low-smoke, halogen-free flame-retardant TPU cable material and a preparation method thereof.
[0006] In the first aspect, the present application provides a low-cast, low-smoke, halogen-free flame-retardant TPU cable material using the following technical solution: a low-cast, low-smoke, halogen-free flame-retardant TPU cable material, comprising the following components in parts by weight: Modified TPU 120 parts; Compatibilizer 10-12 parts; Dispersant 1-10 parts; 15-30 parts of inorganic filler; 2-8 parts of methyl methacrylate; 1-2 parts of silicone masterbatch; Initiator 0.01-0.05 parts; Cross-linking agent 0.05-2 parts; The modified TPU is prepared by the following preparation steps: S1. Precursor compound A is synthesized from hydroquinone dihydroxyethyl ether, diphenylmethane-4,4'-diisocyanate, polytetrahydrofuran ether, and organic phosphorus-containing polyether polyol; S2, mixing the precursor compound A and nano magnesium hydroxide to obtain.
[0007] By adopting the above technical solutions: selecting suitable raw materials and additives, and undergoing a specific preparation process, TPU cable materials with low castability, low smoke and halogen-free flame retardant properties can be obtained. Among them, the preparation of modified TPU and the introduction of nano-magnesium hydroxide are the key factors to achieve the low castability characteristics. The adoption of these technical solutions enables the cable material to have excellent fluidity in the molten state, which can meet the processing requirements in the cable manufacturing process, improve production efficiency and reduce production costs.
[0008] The reason may be that in the preparation process of modified TPU, through the synthesis of specific raw materials, such as hydroquinone dihydroxyethyl ether, diphenylmethane-4,4'-diisocyanate, polytetramethylene ether and organic phosphorus-containing polyether polyol, a TPU precursor compound A with excellent performance can be obtained. The selection of these raw materials makes the TPU molecular chain have more flexible segments and cross-linking points, thereby improving the fluidity and processing performance of TPU; Secondly, the introduction of nano magnesium hydroxide plays a key role in the low castability of modified TPU. The tiny particle size and high specific surface area of nano magnesium hydroxide enable it to form an effective interaction with the TPU molecular chain, enhancing the intermolecular force of TPU. This enhancement enables the modified TPU to better resist the slippage and flow of the molecular chain in the molten state, thereby achieving the characteristics of low castability. In addition, the compatibilizer can improve the compatibility between the components in the cable material, so that the components can better fuse and disperse with each other in the molten state, which helps to reduce the phase separation phenomenon in the cable material and improve the fluidity and processing performance of the cable material. At the same time, the introduction of the dispersant helps to evenly disperse the inorganic filler in the TPU matrix. The uniform dispersion of the inorganic filler can reduce the stress concentration points in the cable material, reduce the flow resistance of the cable material during the processing, and further promote the low flowability of the cable material.
[0009] Preferably, the organic phosphorus-containing polyether polyol in S1 is prepared by ring-opening polymerization reaction of trihydroxymethylphosphine oxide and propylene oxide as main raw materials in the presence of a catalyst, and the phosphorus content of the obtained organic phosphorus-containing polyether polyol is 23-25%.
[0010] By adopting the above technical solution: the introduction of organic phosphorus-containing polyether polyol provides phosphorus-containing elements for TPU cable materials, and phosphorus is an effective flame retardant. When the cable material is heated or encounters a fire source, phosphorus can promote the cable material to form a dense carbonization layer, thereby preventing the further spread of flames and the entry of oxygen. This flame retardant mechanism helps to improve the flame retardant properties of the cable material, so that it can better maintain the integrity of the structure in a fire and reduce the risk of fire; Furthermore, controlling the phosphorus content of the organic phosphorus-containing polyether polyol within the range of 23-25% can ensure that the cable material maintains excellent flame retardant properties without having too much negative impact on the processing properties and mechanical properties of the cable material. Too high a phosphorus content may cause the cable material to become too brittle, while too low a phosphorus content may not achieve the desired flame retardant effect. Therefore, by precisely controlling the phosphorus content, a balance between flame retardant properties and processing properties of the cable material can be achieved. The ring-opening polymerization preparation process of organic phosphorus-containing polyether polyol makes its molecular chain contain both phosphorus elements and polyether chain segments. This structural feature enables it to be better compatible and interact with the TPU molecular chain. This compatibility not only helps to improve the uniformity and stability of the cable material, but also helps to improve the low flowability of the cable material. The introduction of polyether chain segments increases the flexibility and fluidity of the TPU molecular chain, making the cable material easier to flow and process in the molten state.
[0011] Preferably, the molecular polymerization degree of the polytetrahydrofuran ether in S1 is 2000-3000.
[0012] By adopting the above technical solution: when the molecular polymerization degree of polytetramethylene ether is controlled within the range of 2000-3000, its molecular weight is moderate, which not only ensures the sufficient length of the TPU molecular chain, but also avoids the processing difficulties caused by the excessive length of the molecular chain. This moderate molecular weight helps TPU maintain good fluidity in the molten state, thereby achieving the characteristics of low castability; Too high a molecular polymerization degree may cause TPU to become too viscous, which is not conducive to processing, while too low a molecular polymerization degree may reduce the strength and wear resistance of TPU. Therefore, controlling the molecular polymerization degree of polytetramethylene ether within the range of 2000-3000 can ensure the low flowability of TPU cable materials while maintaining its excellent physical and mechanical properties. In addition, the synergistic effect of polytetramethylene ether and other raw materials such as hydroquinone dihydroxyethyl ether, diphenylmethane-4,4'-diisocyanate and organic phosphorus-containing polyether polyols is also the key to achieving low castability. The interaction and reaction between these raw materials can form TPU molecular chains with specific structures and properties, thereby giving the cable material excellent properties such as low castability, low smoke and halogen-free flame retardancy.
[0013] Preferably, the compatibilizer is maleic anhydride grafted polyethylene.
[0014] By adopting the above technical solution: the compatibility between the modified TPU and other components can be significantly enhanced, thereby further optimizing the performance of low-casting, low-smoke halogen-free flame-retardant TPU cable materials.
[0015] Preferably, the dispersant is one or more of phosphate ester and polyacrylate.
[0016] By adopting the above technical solution: phosphate ester and polyacrylate are used as dispersants, which have good wetting and dispersing effects. They can be adsorbed on the surface of inorganic fillers, reduce the interfacial tension between the fillers and the matrix material, and make the fillers more easily dispersed in the matrix material. This uniform dispersion can not only reduce the stress concentration points in the cable material and improve the mechanical properties of the cable, but also improve the processing performance and fluidity of the cable material, which is helpful to achieve the characteristics of low castability; The phosphorus elements or ester-based structures in these dispersants may also participate in the flame retardant reaction of the cable material during combustion, promote the formation of a carbonized layer, and thus improve the flame retardant properties of the cable material.
[0017] Preferably, the inorganic filler is nano-silicate and / or wollastonite.
[0018] By adopting the above technical solution: Nano silicate and wollastonite, due to their high hardness, high melting point and chemical stability, can not only improve the mechanical and wear resistance of the cable, but also optimize its heat exchange and heat dissipation performance. At the same time, their nano-scale size enhances the dispersibility in the TPU matrix, improves the overall uniformity and stability of the cable, and more importantly, their low smoke density and halogen content help to achieve the low-smoke and halogen-free characteristics of the cable, improve the flame retardant properties, and ensure the safety performance of the cable.
[0019] Preferably, the cross-linking agent is any one of dimethylthiodiphenyl diisocyanate and diisocyanate phenylmethane.
[0020] By adopting the above technical solution: dimethylthiodiphenyl diisocyanate and diisocyanate phenylmethane are used as crosslinking agents, which can react with the active groups in the TPU molecular chain to form a crosslinking structure. This crosslinking structure can increase the intermolecular force of the cable material, improve the cohesion and strength of the cable material, and make the cable less likely to break or deform when subjected to external forces. By forming a dense crosslinking network, it can effectively inhibit the molecular chain slippage and decomposition of the cable material when heated or burned, thereby delaying the burning speed of the cable and reducing the generation of smoke. This helps to improve the safety of the cable in extreme situations such as fire; Since dimethylthiodiphenyl diisocyanate and diisocyanate phenylmethane have stable chemical properties and good compatibility with TPU matrix, they will not have a negative impact on the processing performance and low flowability of cable materials. Therefore, they can further improve the crosslinking density and stability of cable materials while maintaining their excellent properties.
[0021] Preferably, the initiator is any one of ammonium persulfate and azobiscyclohexylcarbonitrile.
[0022] By adopting the above technical solution, the processing performance, fluidity and appearance quality of the cable material can be improved, and the safety and reliability of the cable can be improved.
[0023] In the second aspect, the present application provides a method for preparing a low-cast, low-smoke, halogen-free, flame-retardant TPU cable material, which adopts the following technical solution: A method for preparing a low-cast, low-smoke, halogen-free flame-retardant TPU cable material, comprising the following steps: A1. Add compatibilizer, dispersant, inorganic filler, methyl methacrylate and silicone masterbatch into a high-speed mixer according to appropriate proportions, and mix at 500-550 rpm for 25-30 min to obtain a premix; A2. Add the premix, initiator, modified TPU and crosslinking agent into a mixer, mix at 145-160°C for 15-20min to obtain a mixed colloid, put the mixed colloid into a twin-screw extruder, extrude and granulate at a die head temperature of 210-220°C to obtain the obtained product.
[0024] By adopting the above technical solution: a low-casting, low-smoke, halogen-free flame-retardant TPU cable material with excellent performance can be prepared. The cable material not only has low castability, is easy to process and fill, but also has the characteristics of low-smoke, halogen-free flame retardancy, which improves the safety and reliability of the cable. At the same time, by optimizing the ratio of each component and the preparation process, the performance of the cable material can be further adjusted to meet different application requirements.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application modifies TPU, introduces organic phosphorus-containing polyether polyols, and controls the molecular structure and degree of polymerization of the raw materials, so that the cable has the characteristics of low smoke, halogen-free and flame retardant. In the event of a fire, the phosphorus-containing element can promote the cable material to form a dense carbonized layer, preventing the spread of flames and the entry of oxygen, thereby effectively protecting the cable structure and reducing the risk of fire. While maintaining low castability and flame retardant properties, it also maintains excellent physical and mechanical properties; 2. Through specific raw material selection and preparation process, the TPU cable material in this application exhibits excellent fluidity in the molten state, which can meet the processing requirements in the cable manufacturing process, improve production efficiency and reduce production costs. This low cast property helps to reduce defects and waste in the cable manufacturing process and improve product quality. DETAILED DESCRIPTION
[0026] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials.
[0027] Performance testing The masterbatch prepared in the embodiment and the comparative example was selected as the test object, and then the masterbatch was continuously extruded on a twin-screw extruder for 3 hours to observe its casting condition; The tensile strength (MPa) and elongation at break (%) of the masterbatch were tested according to GB / T1040.3; The smoke density of the masterbatch under flameless conditions was tested according to ASTM E662; The flame retardant properties of the masterbatch were tested according to GB / T 24093 and characterized by oxygen index (%).
[0028] Preparation Example 1 A modified TPU, its preparation method is as follows: S1. Precursor compound A is synthesized from hydroquinone dihydroxyethyl ether, diphenylmethane-4,4'-diisocyanate, polytetrahydrofuran ether, and organic phosphorus-containing polyether polyol; S2, mixing the precursor compound A and nano magnesium hydroxide to obtain.
[0029] The organic phosphorus-containing polyether polyol is prepared by ring-opening polymerization reaction with trihydroxymethylphosphine and propylene oxide as main raw materials in the presence of a catalyst, and its phosphorus content is 24%; the molecular polymerization degree of polytetrahydrofuran ether is 2500.
[0030] Preparation Example 2-6 A modified TPU, which is different from Preparation Example 1 in that the use of the organic phosphorus-containing polyether polyol is different, and the specific situation is referred to the following table: Table: Usage of each component in Preparation Examples 2-6 Preparation Example 7 A modified TPU, which is different from Preparation Example 1 in that the modified TPU is prepared by the following preparation steps: S1. Precursor compound A is synthesized from hydroquinone dihydroxyethyl ether, diphenylmethane-4,4'-diisocyanate, polytetrahydrofuran ether, and organic phosphorus-containing polyether polyol; S2. Mix the precursor compound A and nano aluminum hydroxide to obtain. Example
[0031] Example 1 A low-cast, low-smoke, halogen-free flame-retardant TPU cable material, the components and the corresponding amounts of which are shown in the following table, and is prepared by the following preparation method: A1. Add maleic anhydride grafted polyethylene, phosphate, nano-silicate, methyl methacrylate and silicone masterbatch into a high-speed mixer according to an appropriate feeding ratio, and mix at a high speed of 530 rpm for 25 min to obtain a premix; A2. Add the premix, azobiscyclohexylcarbonitrile, the modified TPU obtained in Preparation Example 1, and dimethylthiodiphenyl diisocyanate into a mixer, mix at 150° C. for 20 min to obtain a mixed colloid, put the mixed colloid into a twin-screw extruder, and extrude and granulate at a die head temperature of 215° C. to obtain.
[0032] Table: Components and their weights in Example 1 (kg) The masterbatch prepared in Example 1 was extracted and tested for performance according to the above test standard. The results were averaged. The test results are shown in the following table: Table: Performance test results of Example 1 Test items Example 1 Tensile strength(MPa) 12.4 Elongation at break (%) 560 Smoke density (25kw) 174 Oxygen index (%) 41 Casting Very little casting, starting to occur after 2.5 hours of work As can be seen from the above table, the cable masterbatch prepared in Example 1 has a tensile strength of 12.4 MPa, an elongation at break of 560%, a smoke density of 174, and extremely low castability. All test results are good. It has low smoke, halogen-free and low castability performance, and also has excellent flame retardant properties.
[0033] Analysis of the possible reasons: The polar groups on the modified TPU molecular chain, such as ester groups and ether bonds, form hydrogen bonds or van der Waals forces with the polar groups in components such as phosphate esters and nanosilicates. This interaction not only enhances the compatibility and dispersibility between the components, but also effectively inhibits the flowability of the cable material. This close combination enables the cable material to maintain a stable shape during processing and is not easy to flow, thereby improving the processing efficiency and quality of the cable. Its synergistic effect with other components effectively reduces the flowability of the cable material by enhancing the compatibility, dispersibility and cross-linking density of the components of the cable material, providing a strong guarantee for the high-quality processing and stable use of the cable.
[0034] Embodiment 2-8 A low-casting, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that the amounts of the components are different.
[0035] The master batches prepared in Examples 2-8 were extracted and tested for performance according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of Examples 2-8 It can be seen from the above table that, except for Example 2, Example 3 and Example 6, the casting conditions of the cable masterbatch prepared by the remaining examples are not good, and a large amount of casting occurs after working for 0.5 hours. In addition, the mechanical properties and flame retardant properties of Examples 2-8 are good, and low smoke; In Example 4, the feeding amount of nano-silicate is increased, so that the prepared cable material has better mechanical properties, the tensile strength is 12.8 MPa, the elongation at break is 590%, and the smoke density is slightly increased, which will cause more smoke to appear when the cable material is burned, and it produces more casting after 0.5 hours of startup. When the silicate is excessive, the fluidity of the cable material may be reduced, affecting the smooth progress of the extrusion process.
[0036] In Example 5, as the content of methyl methacrylate increased, the casting performance was poor, and more casting occurred after working for 0.5 hours. This may be because (MMA) is a hard monomer, and its polymer chain has a strong intermolecular force, which increases the overall viscosity and reduces the fluidity, that is, more casting occurs.
[0037] In addition, when the amount of initiator and cross-linking agent increases, it will affect the polymerization reaction rate and process, thereby increasing the cross-linking density of the cable material; when excessive, it may cause its viscosity to increase and its fluidity to decrease, as shown in the test results in Examples 7 and 8.
[0038] Examples 9-13 A low-casting, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that the modified TPU used is from a different source.
[0039] Table: Usage of modified TPU in Examples 9-13 Example Modified TPU Source Example 9 Prepared from Preparation Example 2 Example 10 Prepared from Preparation Example 3 Embodiment 11 Prepared by Preparation Example 4 Example 12 Prepared from Preparation Example 5 Example 13 Prepared from Preparation Example 6 Comparative Example 1 A low-casting, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that the modified TPU used is from Preparation Example 7.
[0040] Comparative Example 2 A low-casting, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that the TPU used is not modified.
[0041] The masterbatches prepared in Examples 9-13 and Comparative Examples 1-2 were selected and tested for performance according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of Examples 9-13 and Comparative Examples 1-2 As can be seen from the above table, the cable masterbatch prepared in Example 9 has a tensile strength of 9.6 MPa, an elongation at break of 480%, a smoke density of 198, an oxygen index of 24%, and severe casting occurs within 0.2 h of startup, and all performances are poor; The modified TPU raw materials prepared in Example 9 are different. Due to the differences in the chemical properties and structures of phenylphosphonic acid and trihydroxymethylphosphine oxide, the newly prepared organic phosphorus-containing polyether polyol may have poor compatibility with other components in the precursor compound A, resulting in increased heterogeneity of the overall structure, thereby reducing the tensile strength and elongation at break of the cable material, and the fluidity and uniformity in the molten state are deteriorated, thereby affecting the casting condition.
[0042] In Comparative Example 2, the tensile strength is 8.2 MPa, the elongation at break is 520%, the smoke density is 195, the oxygen index is 28%, and severe casting occurs within 0.25 h of startup. Since the TPU used is not modified, its various properties are significantly different from those of Example 1 using modified TPU. After modification, TPU will be endowed with better flow properties, machining strength and flame retardancy.
[0043] In addition, when the molecular polymerization degree of polytetrahydrofuran ether, the raw material for preparing modified TPU, is increased to 3000 or decreased to 2000, it will have a certain impact on the obtained cable material masterbatch, which can be seen from Examples 12 and 13. Shorter polymer chains may make the cable material have better fluidity in the molten state, but may also cause a decrease in wetting performance, while longer polymer chains may cause the cable material to have a higher viscosity in the molten state, requiring higher temperature and pressure to achieve a good casting effect. Therefore, the change in molecular polymerization degree has a significant effect on the processing performance of the cable material, which is directly related to the quality of the casting.
[0044] As for Comparative Example 1, in which nano-magnesium hydroxide is replaced by an equal amount of aluminum hydroxide, compared with Example 1, the tensile strength and oxygen index of the cable material are slightly affected, with only a small decrease, while the elongation at break and smoke density are almost not affected. In terms of casting, there may be differences in the physical properties (such as particle size, dispersibility, etc.) between aluminum hydroxide and nano-magnesium hydroxide, which may cause a slight decrease in the flowability of the cable material.
[0045] Embodiment 14 A low-cast, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that: The compatibilizer used is maleic anhydride grafted ethylene-octene copolymer.
[0046] Embodiment 15 A low-cast, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that: The dispersant used is a mixture of phosphate ester and polyacrylate.
[0047] Example 16 A low-cast, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that: The inorganic filler used is a mixture of nano silicate and wollastonite.
[0048] Embodiment 17 A low-cast, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that: The initiator used is a mixture of ammonium persulfate and azobiscyclohexylcarbonitrile.
[0049] Embodiment 18 A low-cast, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that: The crosslinking agent used is a mixture of diisocyanate phenylmethane and dimethylthiodiphenyl diisocyanate.
[0050] Embodiment 19 A low-casting, low-smoke, halogen-free flame-retardant TPU cable material, which is different from Example 1 in that in A2, extrusion granulation is performed when the head temperature is 230°C.
[0051] The master batches prepared in Examples 14-19 were extracted and tested for performance according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of Examples 14-19 As can be seen from the above table, in Examples 14-19, the performances of various properties are relatively balanced, while Examples 15 and 19 have better performance in casting, and the other Examples all have more casting after starting to work for 0.5-0.6; The use of maleic anhydride grafted ethylene-octene copolymer as a compatibilizer may not be as expected as maleic anhydride grafted polyethylene in improving the melt fluidity and wettability of cable materials. Moreover, when the inorganic filler is changed to a mixture of nano-silicate and wollastonite, the nano-silicate has an extremely small particle size and a high specific surface area, which enhances the interaction between it and wollastonite, and is easy to form agglomeration or network structure, forming an uneven distribution or phase separation in the mixture. This unevenness will destroy the continuity of the material and reduce the casting performance. When diisocyanate phenylmethane and dimethylthiodiphenyl diisocyanate are used together, since both are highly active isocyanate compounds with strong reactivity, these isocyanate groups may quickly react with other components (such as hydroxyl groups, amino groups, etc.) in the mixture to form a cross-linked structure, and the cross-linking density of the mixture may increase significantly. High cross-linking density means that the connection between the molecular chains is tighter, which restricts the movement of the molecules and causes the overall fluidity of the mixture to decrease. During the casting process, materials with high cross-linking density are more difficult to spread evenly, and uneven casting or excessive casting is prone to occur.
[0052] In addition, a higher die temperature may help the cable material flow and spread better during the extrusion process, thereby improving its casting condition. However, too high a temperature may also cause problems such as adhesion or blockage of the cable material during the extrusion process. Therefore, the die temperature needs to be carefully controlled to ensure a good casting effect.
[0053] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.
Claims
1. A low cast, low smoke, halogen-free flame retardant TPU cable material, characterized in that: The composition comprises the following components in parts by weight: Modified TPU 120 parts; Compatibilizer 10-12 parts; Dispersant 1-10 parts; 15-30 parts of inorganic filler; 2-8 parts of methyl methacrylate; 1-2 parts of silicone masterbatch; Initiator 0.01-0.05 parts; Cross-linking agent 0.05-2 parts; The modified TPU is prepared by the following preparation steps: S1. Precursor compound A is synthesized from hydroquinone dihydroxyethyl ether, diphenylmethane-4,4'-diisocyanate, polytetrahydrofuran ether, and organic phosphorus-containing polyether polyol; S2, mixing the precursor compound A and nano magnesium hydroxide to obtain.
2. The low cast, low smoke, halogen-free flame retardant TPU cable material according to claim 1, characterized in that: The organic phosphorus-containing polyether polyol in S1 is prepared by ring-opening polymerization reaction of trihydroxymethylphosphine oxide and propylene oxide as main raw materials in the presence of a catalyst. The phosphorus content of the obtained organic phosphorus-containing polyether polyol is 23-25%.
3. The low cast, low smoke, halogen-free flame retardant TPU cable material according to claim 1, characterized in that: The molecular polymerization degree of the polytetrahydrofuran ether in S1 is 2000-3000.
4. The low cast, low smoke, halogen-free flame retardant TPU cable material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyethylene.
5. The low cast, low smoke, halogen-free flame retardant TPU cable material according to claim 1, characterized in that: The dispersant is one or more of phosphate ester and polyacrylate.
6. The low cast, low smoke, halogen-free flame retardant TPU cable material according to claim 1, characterized in that: The inorganic filler is nano silicate and / or wollastonite.
7. The low cast, low smoke, halogen-free flame retardant TPU cable material according to claim 1, characterized in that: The cross-linking agent is any one of dimethylthiodiphenyl diisocyanate and diisocyanate phenylmethane.
8. The low cast, low smoke, halogen-free flame retardant TPU cable material according to claim 1, characterized in that: The initiator is any one of ammonium persulfate and azobiscyclohexylcarbonitrile.
9. The method for preparing the low cast, low smoke, halogen-free flame retardant TPU cable material according to any one of claims 1 to 8, characterized in that: The following preparation steps were adopted: A1. Add compatibilizer, dispersant, inorganic filler, methyl methacrylate and silicone masterbatch into a high-speed mixer according to appropriate proportions, and mix at 500-550 rpm for 25-30 min to obtain a premix; A2. Add the premix, initiator, modified TPU and crosslinking agent into a mixer, mix at 145-160°C for 15-20min to obtain a mixed colloid, put the mixed colloid into a twin-screw extruder, extrude and granulate at a die head temperature of 210-220°C to obtain the obtained product.